The Success Analysis of Internal Audit Implementation on Electronics Through Integrated Instance Accounting System of National Data Communication Application - Ferri Taufik (BPJP - STEI, 2018)
This study aims to determine the effect of system quality, information quality and service quality over the use and satisfaction of users and the implications for the internal audit performance electronically within the Supervisory Board of the Supreme Court of the Republic of Indonesia (Bawas MA RI). The research model used different approaches McLean and DeLone Success Model of Information Systems. This study uses primary data obtained from the collection of instruments completed questionnaires respondents as many as 39 people as the accounting systems agencies integrated data communications applications nationwide (Komdanas) The data analysis in this research through Structural Equation Modeling (SEM) procedures using a Lisrel 8.70 application. The tests performed on the quality of service there is no significant effect on user satisfaction komdanas application integrated accounting system. Seventh, the testing conducted on the use of an integrated accounting system application komdanas significant effect on the performance of the internal audit electronically. Eighth, tests performed on user satisfaction integrated accounting system application komdanas no significant effect on the performance of internal audit electronically.